ANALYZING GREEN SITE MANAGEMENT PRACTICES IN MALAYSIA: TRENDS AND INSIGHTS - Khoo Terh Jing; Chin Yee Ha; Mohd Wira Mohd Shafiei; Radzi Ismail (International Journal of Management Studies)
This research explores the current green site management practices (GSMPs) commonly practiced by contractors. While the construction industry has contributed significantly to Malaysia’s development, it has also raised various environmental concerns. GSMPs are gaining attention as a solution to these issues. Nevertheless, their implementation faces various challenges, such as financial concerns and a lack of knowledge. A qualitative approach was adopted to focus on contractors’ experiences with green practices. Five contractors were randomly selected from the construction sites in Malaysia using the convenience sampling method. These respondents, all at the management level, were well-positioned to provide insights. Data collection continued until no new issues emerged from the interviews. The findings revealed that GSMPs are becoming a current trend within the industry. Contractors are beginning to integrate green practices in their construction activities, focusing on construction site waste management, workforce management, best regulatory practices, site establishment and administration, and site facilities. However, there is a notable lack of awareness and knowledge about these green practices among contractors. The study offers practical implications for the future of GSMPs, highlighting the need for increased understanding and adoption. By elaborating on available practices and their implications, this study aims to encourage broader implementation of GSMPs in construction sites.